2007
DOI: 10.1080/14622200601083467
|View full text |Cite
|
Sign up to set email alerts
|

Minnesota tobacco-free park policies: Attitudes of the general public and park officials

Abstract: A growing number of cities and counties in Minnesota have adopted policies or ordinances that restrict tobacco in outdoor locations. Current policies banning or limiting tobacco use on park and recreation grounds exist in at least 70 communities around Minnesota. However, little is known about the support for such policies. The goal of this project was to learn more about the level of support for tobacco-free park policies in Minnesota. A mail survey was sent to 2,400 randomly selected adult Minnesota resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
4
27
1
1
Order By: Relevance
“…In the study, 84.6% of the participants stated that smoking in the public "outdoor spaces" should be completely prohibited (Table 3). This finding differs from that obtained in the study of Elizabeth et al, [17] in which 53% of the participants stated that smoking should be avoided in all public "outdoor spaces" . However, given the descriptive nature of the study, the limitation of generalization should be considered.…”
Section: Discussioncontrasting
confidence: 56%
“…In the study, 84.6% of the participants stated that smoking in the public "outdoor spaces" should be completely prohibited (Table 3). This finding differs from that obtained in the study of Elizabeth et al, [17] in which 53% of the participants stated that smoking should be avoided in all public "outdoor spaces" . However, given the descriptive nature of the study, the limitation of generalization should be considered.…”
Section: Discussioncontrasting
confidence: 56%
“…Non-smokers are exposed to SHS in outdoor areas also14–16 and any exposure to SHS is harmful, even in outdoor areas with small buffer zone distances (eg, bus stops, sport stadiums, hospital grounds, areas surrounding schools, universities, outdoor bars and restaurants) 17 18. Furthermore, outdoor restrictions on smoking may help make tobacco use less socially acceptable, by establishing positive smoke-free role models for youth7 11 17 19 20 and reducing (youth) opportunities to smoke, fire hazards and the pollution generated by cigarette butts (non-biodegradable litter) in public parks and beaches 7 11 19–21. Thus, extension of smoking regulations to outdoor areas is a relevant tool for tobacco control 13 22 23…”
Section: Introductionmentioning
confidence: 99%
“…36 In a 2004 survey in Minnesota, 34 percent of respondents strongly agreed and 19 percent somewhat agreed that smoking should be prohibited in all outdoor parks at all times. 37 In 2011 the Gallup organization reported that for the first time since it began polling on the issue, a majority (59 percent) of respondents supported banning smoking in all public places. This represented a marked shift from 2008, when only 40 percent had supported such limits.…”
Section: The Denormalization Of Smokingmentioning
confidence: 98%